2022
DOI: 10.1093/ibd/izac071
|View full text |Cite
|
Sign up to set email alerts
|

The T-Cell Response to SARS-CoV-2 Vaccination in Inflammatory Bowel Disease is Augmented with Anti-TNF Therapy

Abstract: Lay Summary T-cell and antibody responses to severe acute respiratory syndrome coronavirus 2 vaccination in inflammatory bowel disease patients are poorly correlated. T-cell responses are preserved by most biologic therapies, but augmented by anti-tumor necrosis factor (anti-TNF) treatment. While anti-TNF therapy blunts the antibody response, cellular immunity after vaccination is robust.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 16 publications
3
27
2
Order By: Relevance
“…These data are in line with observations from CLARITY-IBD, in which T-cell responses were not significantly different between patients treated with infliximab and patients treated with vedolizumab following two doses of vaccine, 6 but we have not recapitulated the findings of the CORALE study, which showed augmentation of T-cell response in recipients of anti-TNF. 32 In the current study, we observed that patients treated with thiopurine, infliximab, thiopurine plus infliximab, ustekinumab, or vedolizumab did not differ significantly from healthy controls in terms of T-cell response. However, tofacitinib treatment was associated with reduced T-cell immunity against spike protein, suggesting that this treatment impairs humoral and cellmediated response to COVID-19 vaccination, which might mark out patients on this treatment as particularly susceptible during future waves of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 43%
“…These data are in line with observations from CLARITY-IBD, in which T-cell responses were not significantly different between patients treated with infliximab and patients treated with vedolizumab following two doses of vaccine, 6 but we have not recapitulated the findings of the CORALE study, which showed augmentation of T-cell response in recipients of anti-TNF. 32 In the current study, we observed that patients treated with thiopurine, infliximab, thiopurine plus infliximab, ustekinumab, or vedolizumab did not differ significantly from healthy controls in terms of T-cell response. However, tofacitinib treatment was associated with reduced T-cell immunity against spike protein, suggesting that this treatment impairs humoral and cellmediated response to COVID-19 vaccination, which might mark out patients on this treatment as particularly susceptible during future waves of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 43%
“…Specifically, B cell responses were reduced in response to the anti-TNFα treatment in patients with rheumatoid arthritis, following the seasonal influenza vaccination [ 47 ]. In contrast to the decreased B cell responses by the TNFa blockade, T cell activity was unaffected [ 38 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“… 16 We did find that anti-TNF therapy was associated with a higher CMIR, as was seen in a previous study. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Those on anti-TNF therapy had an augmented response compared with those on no therapy. 24 These differences among studies may be at least partly explained by differences in the COVID-19 vaccine preparations and the immunization schedules among studies. For example, UK health authorities allowed for an extended dosing interval at the beginning of the pandemic so that the second dose of a COVID-19 vaccine could be administered up to 12 weeks later instead of 3 to 4 weeks after the first dose.…”
Section: Discussionmentioning
confidence: 99%